2012
DOI: 10.1002/sce.21006
|View full text |Cite
|
Sign up to set email alerts
|

Improvements to elementary children's epistemic understanding from sustained argumentation

Abstract: Introduction: Iatrogenic ethmoid skull base (ESB) injury during endoscopic sinus surgery (ESS) is a potentially devastating complication. The height of the ESB can vary substantially and should be assessed during preoperative evaluation of the sinus computed tomography (CT) scan. Methods: The objective of this study is to describe an objective preoperative CT evaluation technique to assist the surgeon in defining the height of the ESB prior to performing ESS. Results: We propose a technique which measures the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
184
0
14

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(209 citation statements)
references
References 65 publications
11
184
0
14
Order By: Relevance
“…(2) 1 None of students is able to complete the justification process. This is consistent with literature showing that, individuals have difficulty in justifying their arguments (Ryu & Sandoval, 2012). Only 52% of participants can make a claim with the familiar science content knowledge.…”
Section: Figure 4: Experimental Group Pre -And Post Test Differences supporting
confidence: 91%
See 1 more Smart Citation
“…(2) 1 None of students is able to complete the justification process. This is consistent with literature showing that, individuals have difficulty in justifying their arguments (Ryu & Sandoval, 2012). Only 52% of participants can make a claim with the familiar science content knowledge.…”
Section: Figure 4: Experimental Group Pre -And Post Test Differences supporting
confidence: 91%
“…Learning to argue is a group of skills which must be practiced in order to be acquired, because it is, generally, difficult to learn (Ryu & Sandoval, 2012). Students can fail in presenting a correct claim, which leads to their failure in constructing counterarguments (Ryu & Sandoval, 2012).…”
Section: Impact Of (Qcej) Strategy On Developing the Skills Of Constrmentioning
confidence: 99%
“…Historically, the focus has been on the delivery of science content, but the new goal of science education is aimed at helping students become scientifically literate citizens who are able to act in ways seen as scientific [3][4] [5]. To achieve this purpose, engaging in science "practices" is centered as a way to construct and evaluate scientific knowledge [1] [4].…”
Section: Introductionmentioning
confidence: 99%
“…There has been a growing interest in this aspect of argumentation in the field of science education (e.g., Manz & Renga, 2017;Monteira & Jiménez-Aleixandre, 2015;Osborne, Erduran & Simon, 2004;Ryu & Sandoval, 2012;Sasseron & Carvalho, 2014;Yun & Kim, 2015). Working with evidence in the classroom has the potential to help students to develop scientific thinking (Jiménez-Aleixandre & Erduran 2008;Kuhn, 1993), and children have opportunities to have contact with aspects of practices involved in the construction of scientific knowledge (Kelly, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have reported students' difficulties in establishing relationships between claim and evidence in an appropriate manner. Moreover, they do not expect/ask their peers to provide evidence to support their claim, nor to refute ideas that are proposed (Berland & Reiser, 2009;Ryu & Sandoval, 2012). Osborne et al (2004) mention other challenges like students tendency to: i) select evidence ignoring data that contradict their claims; ii) oversimplify interpretation of evidence and reach conclusions without enough data; iii) use information that go beyond what is presented to evaluate evidence; and iv) ignore certain information for building their answers.…”
Section: Introductionmentioning
confidence: 99%